Analisis Strategi Komunikasi Digital dalam Meningkatkan Pemahaman Masyarakat Desa terhadap Manfaat Program Makan Bergizi Gratis (MBG) - Aiayah Aisyah; Syahrul Usman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The Free Nutritious Meal (MBG) program is one of the Indonesian government’s initiatives to address nutritional challenges in rural areas. The program’s success is largely determined by the effectiveness of digital communication strategies used to disseminate information to local communities. This study aims to evaluate the extent to which digital communication strategies enhance rural community understanding of the MBG program. The research employed a qualitative case study approach within a post-positivist paradigm. Data were collected through in-depth interviews, participatory observation, document and digital content analysis, and focus group discussions involving village heads, village operators, community leaders, and MBG beneficiaries. Findings show that the use of WhatsApp group discussions combined with government-issued infographics increased community understanding from 32% to 78% among 50 participants, with higher engagement observed among younger adults. The study further developed an integrated digital communication model that incorporates multi-platform outreach, culturally adapted visual messages, and two-way feedback mechanisms. The main contribution of this research lies in providing a validated framework for digital communication in rural contexts. Practically, the study recommends leveraging familiar social media platforms, providing digital literacy training for village operators, and strengthening feedback mechanisms to optimize program dissemination